The power of the sea : tsunamis, storm surges, rogue waves, and our quest to predict disasters - Parker, Bruce B. (Palgrave Macmillan, 2010)
"Classics from Moby Dick to A perfect storm have sought to capture mankind's obsession with the might and the mystery of the sea. The greatest minds for centuries, including Isaac Newton, Napoleon, and Benjamin Franklin, have worked to understand and predict when its next act of destruction will occur. The awesome power of the earth's oceans have been at the forefront of everyone's minds in recent years, from the 2004 Indian Ocean Tsunami (230,000 dead), to the devastation of New Orleans after Hurricane Katrina, to the unknown consequences of the melting of thousands of glaciers as the Earth's temperature slowly rises. Bruce Parker, former Chief Scientist for the National Ocean Service, brings together the breathtaking history of man's relationship with the sea with the latest scientific breakthroughs to explore in this wide-sweeping, fascinating narrative"--